Projeto FutFEB uso da robótica móvel para difusão tecnológica - Bordon, Mário Eduardo [UNESP]; Franchin Marcelo Nicoletti [UNESP]; Castanho, José Eduardo Cogo [UNESP]; Andreoli, André Luiz [UNESP]; Menezes, Thainan Augustinho [UNESP]; Sacchi, Victória Regina [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The FutFEB Extension Project "Use of Mobile Robotics for Technological Diffusion" aims to stimulate the interest of high and fundamental school students to pursue careers in engineering and computer science. Therefore, simple mobile robots are used together with lectures and audiovisual material to awaken the interest of young people to the challenges and attractive aspects of technological careers. The activities are planned to be playful and entertaining whenever possible. Also, the importance of technology in modern life is emphasized. At the same time, the project challenges positively the undergraduate students in electrical engineering to demonstrate and apply their knowledge and skills to build mobile robots for competitions and academic activities.

O Projeto de Extensão FutFEB "Uso da Robótica Móvel para Difusão Tecnológica", tem por objetivo estimular o interesse dos alunos do ensino médio, técnico e fundamental para seguirem carreira nas áreas de engenharia e da ciência da computação. Para tanto, são utilizados robôs móveis simples em conjunto com material didático e audiovisual para despertar de forma lúdica, por meio de palestras e demonstrações práticas, o interesse dos jovens para os desafios e atrativos das carreiras tecnológicas e a importância delas na vida moderna. Ao mesmo tempo o projeto desafia de forma positiva os alunos do curso de graduação em engenharia elétrica a demonstrarem seus conhecimentos e habilidades na construção de robôs móveis para competições e atividades acadêmicas.
Keywords: Technological diffusion; Mobile robotics; University extension; Difusão tecnológica; Robótica móvel; Extensão universitária